The effect of face washing frequency on acne vulgaris patients - Hastuti, Rini; Mustifah, Etty Farida; Ulya, Imroatul; Risman, Muhammad; Mawardi, Prasetyadi (Journal of General - Procedural Dermatology and Venereology Indonesia, 2019)
Background: Patients with acne often wash their faces twice a day, but there are not many studies supporting this practice. Methods: A single-blind randomized clinical trial was conducted in 38 subjects, divided into three groups based on face washing frequency (once, twice, and thrice a day). All groups used the same cleanser. The acne vulgaris severity and the number of lesions were assessed prior to study. After eight weeks, we re-assessed the acne severity, the number of lesions, the adverse event and patient’s self-evaluation. SPSS 17 was used to analyze the face washing frequency and the number of acne lesions. Results: Reduction in the average number of acne lesions was found in once and twice face washing groups, while the thrice group had increased number of acne lesions. The frequency of face washing with the number of lesions provided significant result in group 1,  but  it only  reduced the  number  of  comedones (p value = 0.041). Conclusion: Acne patients with only comedones lesions can be advised to wash their faces once a day.